Computerised mirror therapy with Augmented Reflection Technology for early stroke rehabilitation: clinical feasibility and integration as an adjunct therapy. Issue 15 (17th July 2017) - Hoermann, Simon; Ferreira dos Santos, Luara; Morkisch, Nadine; Jettkowski, Katrin; Sillis, Moran; Devan, Hemakumar; Kanagasabai, Parimala S.; Schmidt, Henning; Krüger, Jörg; Dohle, Christian; Regenbrecht, Holger; Hale, Leigh; et al.
Abstract: Purpose: New rehabilitation strategies for post-stroke upper limb rehabilitation employing visual stimulation show promising results, however, cost-efficient and clinically feasible ways to provide these interventions are still lacking. An integral step is to translate recent technological advances, such as in virtual and augmented reality, into therapeutic practice to improve outcomes for patients. This requires research on the adaptation of the technology for clinical use as well as on the appropriate guidelines and protocols for sustainable integration into therapeutic routines. Here, we present and evaluate a novel and affordable augmented reality system (Augmented Reflection Technology, ART) in combination with a validated mirror therapy protocol for upper limb rehabilitation after stroke. Method: We evaluated components of the therapeutic intervention, from the patients' and the therapists' points of view in a clinical feasibility study at a rehabilitation centre. We also assessed the integration of ART as an adjunct therapy for the clinical rehabilitation of subacute patients at two different hospitals. Results: The results showed that the combination and application of the Berlin Protocol for Mirror Therapy together with ART was feasible for clinical use. This combination was integrated into the therapeutic plan of subacute stroke patients at the two clinical locations where the second part of this research was conducted. Conclusions: Our findings pave the way for using technology to provide mirror therapy in clinical settings and show potential for the more effective use of inpatient time and enhanced recoveries for patients. Implications for Rehabilitation: Computerised Mirror Therapy is feasible for clinical use Augmented Reflection Technology can be integrated as an adjunctive therapeutic intervention for subacute stroke patients in an inpatient setting Virtual Rehabilitation devices such as Augmented Reflection Technology have considerable potential to enhance stroke rehabilitation